Ethnobotanical study on medicinal plant used by Sungai ethnic along middle streem Bongkoka river, Pitas, Sabah / Norfalahani Sulaiman - Sulaiman, Norfalahani (2017)
Ethnobotany is a relationship between plant and human. This study had done to determine and identify the medicinal plants used by Sungai ethnic along, Middle Stream of Bangkoka River, Pitas, Sabah. Results for this study, from interviews of five villages found that 65 plants from 39 families of medicines used by Sungai ethnics in Pitas,, could treated 41 diseases. Decoction of leaves and roots are commonly used to treat diseases. Also the plant status, growth form, frequency and lifespan of medicinal plants was found. The classification of dichotomous key are constructed which one kingdom, one phylum, two class, nine subclass, 28 order, 39 family, 65 genus and 65 species. Moreover, in the Economic Index Value ( EVI ) , Bowing, Binterung, Kempayas, Durian Belanda, Halia, Kelapa, Kunyit, Lada korok, Peria Hutan, Pinang, Serai, dan Tawadak are the 14 species of medicinal plants sold in Pitas Market and their highest Economic Index Value ( EVI ) is the Durian belanda (Annona muricata L ) and Kempayas (Carica papaya Linn). The documented information from this study can be used for further studies on phytochemical confirmation.